Significance of serum antibodies against HSP 60 and HSP 70 for the diagnostic of infectious diseases - Bleotu, Coralia (Virulence, 2014)
Heat shock proteins (HSP) represent important antigenic targets for the immune response, playing an important role in the pathology and infectious diseases control. The purpose of this work was to investigate the levels of HSP60 and HSP70 specific antibodies in the bloodstream of patients with different bacterial infections and cancer, in order to evaluate their potential role as diagnosis markers of different infectious diseases. Detection of specific anti-HSP 60 and HSP 70 serum levels was performed by ELISA. Statistical analysis of data by multivariate logistic regression was performed using GraphPadPrism software and statistical tests based on chi-square and Student t-test. High levels of anti-HSP60 were found in patients with localized infections, while the levels of anti- HSP70 were higher in the group with generalized infections. The serum levels of both anti-HSP 60 and anti-HSP70 were significantly increased in patients with Gram-negative bacterial infections, as compared with patients harbouring infections produced by Gram-positive and fungal strains, demonstrating their potential use as additional diagnosis and prognosis markers in infections with this etiology.